Low-Density Parity-Check Codes: Celebrating Receipt of Japan Prize by Prof. Robert G. Gallager - UCHIKAWA, Hironori (Denshi Jouhou Tsuushin Gakkai Kiso, Kyoukai Sosaieti fundamentals review, 2021)
Robert G. Gallager, Professor Emeritus at Massachusetts Institute of Technology, was awarded the 2020 Japan Prize. The low-density parity-check code (LDPC code), the award's subject, is an error correction code proposed by Professor, Gallager in his doctoral thesis in 1960. It has now become an essential fundamental technology that supports our modern digital life. In this article, we describe the LDPC codes that can derive the optimal decoding algorithm in probabilistic inference. Furthermore, in this article we also introduce a practical LDPC code construction.